Scaling Up Small-Scale Agro-Industries: Strategic Marketing Priorities for Sustainable Competitive Advantage - Bagus Putu Yudhia Kurniawan; Dian Rizky; Datik Lestari; Andarula Galushasti; Retno Sari Mahanani; Ida Adha Anrosana Pongoh (Journal of Business Management, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the agroindustry sector play a vital role in economic growth in developing countries. Although capable of producing high-quality, preservative-free food commodities, many traditional agroindustries face stagnation in business scaling up due to limited human resource capabilities, particularly in the field of digital marketing. This study aims to formulate the most optimal marketing strategy priorities for a local banana chip agroindustry in East Java, Indonesia. Using a quantitative descriptive approach, this study integrates the Internal Factor Evaluation (IFE) matrix, the External Factor Evaluation (EFE) matrix, the Internal-External (IE) matrix, SWOT analysis, and the Quantitative Strategic Planning Matrix (QSPM). Data collection involved assessments by experts and practitioners, with instrument weighting using the Paired Comparison technique to ensure evaluation precision. The research results validate solid internal strengths with an IFE score of 2.96 and the ability to respond to external conditions with an EFE score of 2.69, positioning the agroindustry in Quadrant V (Hold and Maintain / Grow and Build) on the IE Matrix. The most crucial finding from the QSPM analysis demonstrates that the highest-priority strategy, with a Total Attractiveness Score (TAS) of 7.42, is not the modification of physical products but rather the addition of specialized personnel in the field of marketing. This finding contributes to the literature on SME strategic management by confirming that a shift from conventional operational management toward functional specialization (digital marketing) is an absolute prerequisite for expanding market reach and maintaining a competitive advantage.